Urothelium – the brain of the urinary bladder. Will knowing its properties pave the way for creating a tissue-engineered bladder? - Wolny, Agnieszka; Hyla-Klekot, Lidia; Pastuszka, Agnieszka; Kudela, Grzegorz; Koszutski, Tomasz (Pediatria Polska - Polish Journal of Paediatrics, 2019)
The neurogenic bladder is a polyaetiological disease syndrome. It results from changes in the central and peripheral nervous system and, so far, has been mainly regarded at the macroscopic level. An increasing number of recent studies have pointed, however, to the role of intact bladder innervation also at the cellular level. At present, urothelium is considered not only as a tight barrier but also as a complex structure controlling the activity of the urinary bladder due to multiple connections with the nervous, endocrine, and immune systems. As a result of denervation, the biological processes taking place in urothelium are disturbed. Understanding of such signalling pathways could contribute significantly to effective pharmacological treatment of neurogenic bladder dysfunction. Moreover, it may contribute to the creation of a bio-organ that could potentially replace a dysfunctional urinary bladder in such patients.